A Study on Consumption Patterns, Preference and Satisfication of Instant Food Products Among Young Adults with Reference to Coimbatore City - S.J Sembakalakshmi, S.J Sembakalakshmi; S. Nirmala, S. Nirmala (Journal of Neonatal Surgery, 2025)
The growing demand for convenience and time-saving food options has led to a significant rise in the consumption of instant food products among young adults. This study explores the consumption patterns, preferences, and satisfaction levels of young consumers toward instant food products. It examines key factors such as taste, price, nutritional value, brand perception, and convenience that influence purchasing decisions. Additionally, the research investigates the role of marketing strategies, social media influence, and packaging in shaping consumer preferences. The findings provide insights into young adults' attitudes toward instant food and offer recommendations for brands to enhance product offerings, improve customer satisfaction, and foster brand loyalty in this competitive marke.